SPECIFIC CLASSIFICATION FEATURES OF INTERMEDIARY ENTREPRENEURSHIP - I.Rajabboev (EPRA International Journal of Research and Development (IJRD), 2022)
The article provides information and recommendations on the specific classification features of brokerage business.